2015
DOI: 10.1371/journal.pone.0139260
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Leukocyte Response in Acute Vocal Fold Injury

Abstract: Macrophages location in the superficial layer of the vocal fold (VF) is not only at the first line of defense, but in a place of physiologic importance to voice quality. This study characterizes and compares macrophage function in two models of acute injury. Porcine VF injuries were created bilaterally by either surgical biopsy or lipopolysaccharide (LPS) (1.5μg/kg) injection. Animals were sacrificed at 1- or 5-day post LPS or 3-, 7-, or 23-days post-surgical injury (n = 3/time/ injury). Flow cytometry charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…To confirm that cell death occurred, we found that the vocal fold epithelium expressed an immunohistochemical marker for apoptosis using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining (11). These findings are in agreement with the previously reported effects of mechanical trauma on cell death in vocal fold fibroblasts (1214). Collectively, the literature suggests that apoptosis may be a natural biological response to vocal fold vibration and may therefore contribute to maintaining a normal epithelial barrier.…”
Section: Introductionsupporting
confidence: 93%
“…To confirm that cell death occurred, we found that the vocal fold epithelium expressed an immunohistochemical marker for apoptosis using terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining (11). These findings are in agreement with the previously reported effects of mechanical trauma on cell death in vocal fold fibroblasts (1214). Collectively, the literature suggests that apoptosis may be a natural biological response to vocal fold vibration and may therefore contribute to maintaining a normal epithelial barrier.…”
Section: Introductionsupporting
confidence: 93%
“…In order to establish cell phenotypes consistent with scar and short‐term biomaterial‐insertion, activation media containing LPS and TGF‐β1was used . We have previously demonstrated that this activation induces normal VFF to take on characteristics of a fibrotic phenotype, and AMO to take on phenotype similar to that seen in chronic scar as well as many biomaterial‐treated dermal wounds (loosely, a phenotype between the traditional pro‐ and anti‐inflammatory classifications).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, macrophages contribute to fibrosis through the production of many of these proteins, although the specific contribution of each is difficult to discern for reasons denoted in the “Introduction”. Previous studies related to characterizing macrophage phenotype (in response to cytokines or in vocal fold injuries) only examined two to three AMO markers, usually limited to a specific role (i.e. inflammation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on normal human vocal folds have shown that tissue‐resident macrophages exist in the superficial layer of the lamina propria and respond to mucosal irritants in children and adults . Recent investigations have demonstrated that pan‐macrophage marker‐positive macrophages increased in the entire lamina propria from 12 hours through 7 days postinjury and return to baseline 2 to 4 weeks postinjury in injured rat vocal folds, and M2 marker‐positive macrophages increased in injured porcine vocal folds . However, the phenotypic or distributional changes in macrophages in the vocal fold during wound healing have not been well investigated.…”
Section: Discussionmentioning
confidence: 99%